Internal Assessments for the publishing house Aufbau in the German Democratic Republic: A Glimpse into Elga Abramowitz’s Vorlass - Rotroff, Heidi R. (chronotopos – A Journal of Translation History, 2025)
Elga Abramowitz, editor and translator, worked mainly for the Aufbau publishing house in the German Democratic Republic (GDR) from 1952 to 1990. During her time there, she was responsible for a variety of tasks within the publishing house. Through the preservation of her Vorlass, we have the opportunity to explore her varied work. In particular, this article focuses on the assessments she wrote for Aufbau-Verlag – not the much-discussed assessments for the print permit process, but assessments written to determine the suitability of works for publication in Aufbau-Verlag. These documents were intended for internal use within the publishing house and can offer some insight into assessment and publishing processes in the German Democratic Republic’s publishing houses, particularly the Aufbau-Verlag. One of the most interesting finds is that often, the quality rather than the ideological content of the texts seemed to be a determining factor regarding which books were recommended for publication.